EVALUATION OF PHYTOCHEMICAL CONSTITUENTS AND ANTIMICROBIAL ACTIVITY OF SILVER NANOPARTICLE SYNTHESIZED IPOMOEA NIL AGAINST SELECTED PATHOGENS - S, Asha; A, Asha; S, Rajeshkumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The objective of this study is to investigate a simple and feasible approach for the production of silver nanoparticles (AgNPs) by using leaf extract of Ipmoea nil and to evaluate its antibacterial activity. Methods: The AgNPs synthesized was characterized by a change in color and the absorption peaks by ultraviolet-visible spectroscopy. The phyto compounds responsible for the reduction and capping of silver ions was known from Fourier transform infrared spectra and phytochemical analysis. The antibacterial effects of prepared aqueous AgNPs were detected against five types of pathogenic bacteria, including Gram-negative and Grampositive bacteria (Escherichia coli, Salmonella, Bacillius, Proteus, and Klebsilla pneumonia) using agar well diffusion method. Results: A peak absorption value between 400 and 450 nm and the color change of the extract from yellowish to red wine were corresponds to the plasmon absorbance of AgNPs. On the other hand, aqueous extract of I. nil mediated AgNPs found to be effective against tested microorganisms (Salmonella, Bacillus, and Proteus) with inhibition zone in the range of 10-13 mm (20 Î¼l and 10 Î¼l) except E. coli and K. pneumonia. Furthermore, aqueous extract of I. nil leaves had no ability to suppress the growth of the tested microorganisms in the concentration of 10 Î¼l. The control also produced similar inhibition zones like AgNPs. Conclusions: Our findings indicated that green synthesized AgNPs mediated by I. nil leaf extract had an efficient anti-bactericidal activity against the bacterial species tested. Hence, further studies are needed to highlight its mechanism and application as an antibacterial agent. Keywords: Ipomoea nil, Silver nanoparticles, Antibacterial activity, Bacteria.